New Identity of the Kimberlite Melt: Constraints from Unaltered Diamondiferous Udachnaya –East Pipe Kimberlite, Russia - Kamenetsky, Vadim S.; Kamenetsky, Maya B.; Maas, Roland (IntechOpen, 2011)
None